Penelitian Atas Penelitian Seni dan Desain: Suatu Studi Kerangka Filosofis-Paradigmatis Bagi Penelitian Seni dan Desain Visual - Karna Mustaqim; D. Rio Adiwijaya; Ferdinand Indrajaya (Bina Nusantara University, 2013)
This paper discusses philosophical framework of practice-based artistic research within the field of art and design in contrast with research in the natural and social science. It is stated that paradigm of artistic inquiry is ilustrated with the role of practicioner as researcher wherein subjectivity, involvement and reflexivity are acknowledged, while (k)nowledge is negotiated – inter-subjective, context bound, and is a result of personal construction. Visual objects have been exhausting large amount of our physical and emotional energy in seeing it which certainly gives them a central role in contemporary ages. It is suggested that research could become part of the needs for experience, to inspire, or to collectively develop a profession. Recently, research as knowledge production has been increasing and gaining its interest within the creative art field. However, there is a foundation which underpins a research, at least some implicit philosophical assumptions of it, which serve as the basis of understanding of reality (ontology), and how to know and justify it (epistemology); and by explicating it, it is believed that scrupulous consideration of it may contribute practical benefits in conducting art and design research. In that regard, this paper presents ontological outlook of Heidegger and also epistemology of art of Merleau-Ponty – which rises within phenomenological tradition – as a philosophical framework which can serve as paradigmatic underpinning of artistic research, in contrast with objectivist approach already identical with research in general.